Preparation, antibacterial and antioxidant properties of green tea seed oil nanoemulsions by self‐emulsification method. (23rd October 2019) - Xu, Wei; Zhu, Dandan; Xu, Bin; Huang, Lu; Xiong, Yongzhao; Ge, Peipei; Wang, Zhao
Abstract : Application of tea oil in food products has been gained more and more attention for its nutritional advantages and functional properties. This research fabricated green tea seed oil nanoemulsions by the self‐emulsification method through variation of oil and surfactant composition. Finally, in vitro antibacterial assay and antioxidant properties were investigated. The results showed that the sizes could be regulated through surfactant content (5–15 wt%) and composition (HLB 10.72–13.93) from 16.44 ± 0.01 nm to 329 ± 4.74 nm. With the increase of the content of green tea seed oil, the DPPH and total antioxidant capacity of the nanoemulsions were gradually improved. Meanwhile, the antibacterial assay was enhanced as the content of green tea seed oil increased from 0.5 to 1.5%. The inhibition zone increased continually to 7.56 ± 0.40 mm and 6.85 ± 0.59 mm when 1.5% oil was provided. The results could provide a reference to essential oils in the design of functional food‐grade ingredients.